Anatomical location of metastatic lymph nodes: an indispensable prognostic factor for gastric cancer patients who underwent curative resection. (1st February 2018) - Zhao, Bochao; Zhang, Jingting; Zhang, Jiale; Chen, Xiuxiu; Chen, Junqing; Wang, Zhenning; Xu, Huimian; Huang, Baojun
Abstract: Background: Although the numeric-based lymph node (LN) staging was widely used in the worldwide, it did not represent the anatomical location of metastatic lymph nodes (MLNs) and not reflect extent of LN dissection. Therefore, in the present study, we investigated whether the anatomical location of MLNs was still necessary to evaluate the prognosis of node-positive gastric cancer (GC) patients. Methods: We reviewed 1451 GC patients who underwent radical gastrectomy in our institution between January 1986 and January 2008. All patients were reclassified into several groups according to the anatomical location of MLNs and the number of MLNs. The prognostic differences between different patient groups were compared and clinicopathologic features were analyzed. Results: In the present study, both anatomical location of MLNs and the number of MLNs were identified as the independent prognostic factors ( p  < .01). The patients with extraperigastric LN involvement showed a poorer prognosis compared with the perigastric-only group ( p  < .001). For the N1–N2 stage patients, the prognostic discrepancy was still observed among them when the anatomical location of MLNs was considered ( p  < .05). For the N3-stage patients, although the anatomical location of MLNs had no significant effect on the prognosis of these patients, the higher number of MLNs in the extraperigastric area was correlated with the unfavorable prognosis ( p  < .05). Conclusion: The anatomical location of MLNs was an important factor influencing the prognostic outcome of GC patients. To provide more accurate prognostic information for GC patients, the anatomical location of MLNs should not be ignored.